Does the impaired postural control in Parkinson's disease affect the habituation to non-sequential external perturbation trials? - Beretta, Victor Spiandor [UNESP]; Carpenter, Mark Gregory; Barbieri, Fabio Augusto [UNESP]; Santos, Paulo Cezar Rocha [UNESP]; Orcioli-Silva, Diego [UNESP]; Pereira, Marcelo Pinto [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Elsevier, 2021)
Background: How people with Parkinson's disease habituate their postural response to unpredictable translation perturbation is not totally understood. We compared the capacity to change the postural responses after unexpected external perturbation and investigated the habituation plateaus of postural responses to non-sequential perturbation trials in people with Parkinson's disease and healthy older adults. Methods: In people with Parkinson's disease (n = 37) and older adults (n = 20), sudden posterior support-surface translational were applied in 7 out of 17 randomized trials to ensure perturbation unpredictability. Electromyography and center of pressure parameters of postural response were analyzed by ANOVAs (Group vs. Trials). Two simple planned contrasts were performed to determine at which trial the responses first significantly habituate, and by which trials the habituation plateaus. Findings: Older adults demonstrated a first response change in trial 5 and habituation plateaus after trial 4, while for people with Parkinson's disease, the first change occurred in trial 2 and habituation plateau after trial 5 observed by center of pressure range. People with Parkinson's disease demonstrated a greater center of pressure range in trial 1 compared to older adults. Independent of trial, people with Parkinson's disease vs. older adults demonstrated a greater ankle muscle co-activation and recovery time. Interpretation: Despite the greater center of pressure range in the first trial, people with Parkinson's disease can habituate to unpredictable perturbations. This is reflected by little, to no difference in the time-course of adaptation for all but 2 parameters that showed only marginal differences between people with Parkinson's disease and older adults.
Keywords: Adaptation; Balance control; Center of pressure; Movement disorders; Support-base translation